2020
DOI: 10.3390/app10155307
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the Integration of Heliostat Solar Receiver to Gas and Combined Cycles by Energy, Exergy, and Economic Point of Views

Abstract: Due to the high amount of natural gas resources in Iran, the gas cycle as one of the main important power production system is used to produce electricity. The gas cycle has some disadvantages such as power consumption of air compressors, which is a major part of gas turbine electrical production and a considerable reduction in electrical power production by increasing the environment temperature due to a reduction in air density and constant volumetric airflow through a gas cycle. To overcome these weaknesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…The efficiency of the ORC turbine and pumps are considered to be 85% [39,41] • For the heat exchanging components such as the condenser and the evaporator, energy effectiveness is assumed to be 85% [1,39] •…”
Section: System and Process Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The efficiency of the ORC turbine and pumps are considered to be 85% [39,41] • For the heat exchanging components such as the condenser and the evaporator, energy effectiveness is assumed to be 85% [1,39] •…”
Section: System and Process Descriptionmentioning
confidence: 99%
“…Heat loss of components is assumed around 3% of the energy released by the hottest steam at these components [1,39] The solar radiation and wind turbine modelling are presented in Appendix A.…”
Section: System and Process Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been reported in recent years on energy, exergy, economic and environmental analyses, and optimization of various power generation systems, including combined heat and power, renewable energy, and other plants [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%